2012
DOI: 10.1093/deafed/ens026
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Classroom Environment to Increase Engagement and Decrease Disruption with Students Who Are Deaf or Hard of Hearing

Abstract: The goal of this study was to examine the effect of physical modifications on the academic engagement and disruptive behavior of Deaf or Hard-of-Hearing students in self-contained classrooms. Three classrooms at a school for the Deaf were modified after consultation with the classroom teachers. The modifications of the classroom environment included changes in seating arrangements, classroom organization, visual stimulation, and acoustic quality. A multiple-baseline design was used to examine the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…Teachers have reported that physical classroom modifications that improve acoustics (e.g., laying carpet/rugs on hard surface flooring, using caps on chair legs) take little time to implement, are sustainable over time, and improve student behavior (Guardino & Antia, 2012). After modifying the acoustic learning environment, it is recommended that the efficacy of the modifications be measured, a role for which the smartphone application would be ideal (Crandell, Kreisman, Smaldino, & Kreisman, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers have reported that physical classroom modifications that improve acoustics (e.g., laying carpet/rugs on hard surface flooring, using caps on chair legs) take little time to implement, are sustainable over time, and improve student behavior (Guardino & Antia, 2012). After modifying the acoustic learning environment, it is recommended that the efficacy of the modifications be measured, a role for which the smartphone application would be ideal (Crandell, Kreisman, Smaldino, & Kreisman, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Listening in noise is a barrier to participating in conversation for many people, however of great concern is that research also indicates that students for whom English is an additional language, and those with speech and language difficulties, learning difficulties, cognitive disorders, attention disorders and behavioural problems also have difficulties listening and interpreting speech in noisy learning spaces (Massie & Dillon, 2006;Rowe & Pollard, 2003;Sharma, Purdy, & Kelly, 2009;Shield, Greenland, & Dockrell, 2010;Smaldino & Flexer, 2012;Snow & Powell, 2008). It is also widely reported that noisy environments adversely affect students with sensory disorders such as autism and vision loss by impacting cognition, heightening anxiety and diminishing access to clear speech (Anderson, 2001;Clark & Sorqvist, 2012;Guardino & Antia, 2012;Katte, Bergstroem, & Lachmann, 2013;Smaldino & Flexer, 2012). Collectively for the purpose of this research this cohort is referred to as students with hearing difficulties.…”
Section: The Problemmentioning
confidence: 99%
“…Further research indicates that students for whom English is an additional language, and those with speech and language difficulties, learning difficulties, cognitive disorders, attention disorders and behavioural problems also have difficulties listening and interpreting speech in noise (Massie & Dillon, 2006;Rowe, Rowe, & Pollard, 2004;Sharma et al, 2009;Shield, Greenland, & Dockrell, 2010;Smaldino & Flexer, 2012;Snow & Powell, 2008). It is also widely reported that noisy environments adversely affect students with sensory disorders such as autism and vision loss by impacting cognition, heightening anxiety and diminishing access to clear speech (Anderson, 2001;Clark & Sorqvist, 2012;Guardino & Antia, 2012;Katte, Bergstroem, & Lachmann, 2013;Smaldino & Flexer, 2012).…”
Section: Background: 21st Century Students With Hearing Difficultiesmentioning
confidence: 99%
“…The connection arises as educational institutions must account for the quality of services provided, in terms of quality of education (effectiveness), value for money (efficiency), equity and access ("Australian Education Act 2012," 2012). Building compliance and legislated regulations can be used highly effectively to Meet Student Need, for example, provision of appropriate hearing access solutions and listening environments for hearing impaired students and students with additional sensory needs such as autism and vision loss (Guardino & Antia, 2012;Hooge et al, 2012;Hyde & Palmer, 2010). Figure 1 gives an overview of current legislative initiatives underpinned by human rights movements that aim to enhance accessibility to quality experiences for people with differences (disability) in public meeting spaces in Australia.…”
Section: Figure Policy and Governance And The Impacts Upon Individualsmentioning
confidence: 99%